Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1017/s0022029917000851
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation ofStaphylococcus aureusstrains isolated from mastitis bovine milk in Argentina

Abstract: The study reported in this Research Communication was conducted to characterise Staphylococcus aureus isolates recovered from mastitic bovine milk from dairy herds in Argentina. A total of 829 mastitic milk samples, both clinical and subclinical, were collected from 21 farms by veterinarians and submitted to the laboratory for testing from which 229 S. aureus isolates were recovered, an isolation rate of 28·1%. These isolates were tested for susceptibility to the antibiotics penicillin, erythromycin and clinda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 20 publications
6
19
1
1
Order By: Relevance
“…We also showed that one S. aureus strain was widespread in the two herds investigated, although the herds are geographically distant; this S. aureus strain was responsible for almost all IMIs, probably because it is well adapted to the udder, leading to the persistence of IMIs. Thus, our results are in agreement with other reports that indicated that few specialized S. aureus types with broad geographic distribution are responsible for most of the IMIs in dairy herds (Srednik et al 2018).…”
Section: Resultssupporting
confidence: 94%
“…We also showed that one S. aureus strain was widespread in the two herds investigated, although the herds are geographically distant; this S. aureus strain was responsible for almost all IMIs, probably because it is well adapted to the udder, leading to the persistence of IMIs. Thus, our results are in agreement with other reports that indicated that few specialized S. aureus types with broad geographic distribution are responsible for most of the IMIs in dairy herds (Srednik et al 2018).…”
Section: Resultssupporting
confidence: 94%
“…These isolates were all grouped into CC97. This lineage is prevalent among bovine mastitis isolates from Algeria (Akkou et al ), from Brazil (Rabello et al ), the United Kingdom (Sung et al ), Tunisia (Ben Said et al ), China (Li et al ) and Argentina (Srednik et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Influences from breed, age and lactation stage of the animal have been described (Haftu et al ; Oliveira et al ). Staphylococcus aureus is one of the most important bacterial pathogens causing bovine mastitis (Tenhagen et al ; Wang et al ; Lundberg et al ; Srednik et al ). Mastitis caused by this bacterium has a lower cure rate than for most of the other bacteria (Sartori et al ; Srednik et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Только у 7 выделенных штаммов (6,8 %) выявили чувствительность ко всем исследуемым антибиотикам, тогда как 96 изолятов оказались устойчивы по крайней мере к одному из них. Другими авторами было установлено очевидное развитие резистентности S. aureus к пенициллину, ампициллину, эритромицину (40,42,43 Устойчивости к оксациллину и цефокситину у всех исследованных нами штаммов мы не обнаружили, что позволяет отнести их к метициллин-чувствительным S. aureus MSSA. В случае MSSA считается, что пенициллин превосходит по действию оксациллин, но только если штаммы не продуцируют пенициллиназу (48).…”
unclassified